(untitled) (مجلة المنصور, 2022)
This paper presents a Genetic Algorithm (GA)- based electronic Proportional-Integral-Derivative (PID) Controller tuner. The tuning is based upon the maximization of a comprehensive fitness function constructed as the inverse of Peak Overshoot (Mp). This approach has a some advantages, it gives a clearer and simpler representation of the problem, simplifies chromosome construction, and totally avoids using binary encoding and decoding so as to simplify software programming. This paper addresses to demonstrate the capability of GA’s to solve complex and constraint optimization Problems via utilizing GA’s as a general-purpose optimizing tool to solve different Control system design problems.